2008
DOI: 10.1093/brain/awn317
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary, spontaneous and reflex blinking in patients with clinically probable progressive supranuclear palsy

Abstract: Patients with progressive supranuclear palsy (PSP) often have blinking abnormalities. In this study we examined the kinematic features of voluntary, spontaneous and reflex blinking in 11 patients with PSP and healthy control subjects. Patients were asked to blink voluntarily as fast as possible; spontaneous blinking was recorded during two 60 s rest periods; reflex blinking was evoked by electrical stimulation of the supraorbital nerve. Eyelid movements were recorded with the SMART analyzer motion system. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 42 publications
4
74
2
1
Order By: Relevance
“…Other methods include home video camera recording [5,6] and tracking the displacement of a reflective marker taped onto a subject's upper eyelid using infrared cameras License http://creativecommons.org/licenses/by/3.0/, which permits unrestricted use, provided the original author and source are credited. [4]. In this work, a high-speed video camera was used to study the rapid eye motion of the voluntary blink.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods include home video camera recording [5,6] and tracking the displacement of a reflective marker taped onto a subject's upper eyelid using infrared cameras License http://creativecommons.org/licenses/by/3.0/, which permits unrestricted use, provided the original author and source are credited. [4]. In this work, a high-speed video camera was used to study the rapid eye motion of the voluntary blink.…”
Section: Introductionmentioning
confidence: 99%
“…A high-speed camera does not require such devices, and hence it can be considered to be more convenient for both participants and researchers. Furthermore, the relatively high palpebral aperture measurements [4,9] may also reflect inaccuracies in measurement techniques that involve attaching either tape or coils to the upper eyelid, which may have only approximated the lid margin position. In contrast, more accurate and reliable results could be obtained from high-speed camera images as no extra eye weight, which might affect the blink dynamics, is involved and also the apparent palpebral aperture between the upper and lower eyelids is measured on a sequential series of images, whereas the coil marker is usually attached about 1 mm above the lid margin.…”
mentioning
confidence: 99%
“…Whether spontaneous blink generator overactivation depends on altered descending control from basal ganglia or on altered projections from mesial frontal areas to basal nuclei remains unclear. The normal blink reflex recovery cycle (a variable known to be abnormal in several basal ganglia diseases) 16,33 argues against a basal ganglia dysfunction. Consistent with the observation that in patients with movement disorders low dopamine levels determine a reduced BR and enhanced R2 recovery index, 33 the correlation between BR and R2 recovery index further supports the hypothesis that the brainstem neural circuits for the BR differ from those for the R2 recovery cycle.…”
mentioning
confidence: 99%
“…The origin of blink triggers, as well as the neurological basis for kinematics, was hypothesized to be the same in the two positions; however, the kinematic behaviors of the eyelids were observed to be strongly modifi ed by the supine position in addition to the previously reported aging eff ect (Sun, Baker, Rouholiman, Hasan, Caza, & Stava, 1997). Certain eyeblink characteristics, even when in a sitting position, suggest specifi c neurological problems such as Parkinson's disease (Agostino, Bologna, Dinapoli, Gregori, Fabbrini, Accornero, et al, 2008) or progressive supranuclear palsy (Bologna, Agostino, Gregori, Belvisi, Ottaviani, Colosimo, et al, 2009). In addition, the present study suggested that the supine position also affects the blink waveform attributes.…”
Section: Discussionmentioning
confidence: 99%